PENGARUH WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA PT. KEDAUNG MEDAN INDUSTRIAL LTD - Anwar Fauzi, Rukmini, Sari Wulandari (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2020)
This research entitled "The Effect of Word of Mouth on Product Purchase Decisions at PT. Kedaung Medan Industrial LTD ". The purpose of this study was to determine the effect of word of mouth on product purchasing decisions and to find out how much influence word of mouth has on product purchasing decisions at PT. Kedaung Medan Industrial LTD. The sample in this study was buyers at PT. Kedaung Medan Industrial LTD, amounting to 50 people. The data collection technique used is using a questionnaire given to each respondent. Data is processed using SPSS version 20.0 for Windows. The data analysis technique used is simple linear regression. The results of a simple linear regression test obtained the equation Y = 0.182 + 1.006 X + e, where word of mouth has a significant effect on the variable purchasing decisions. The determinant coefficient (R2) is obtained at 0.646 or 64.6%, which means that the word of mouth variable influences the product purchase decision, t test (partial), word of mouth or variable (X) has a tcount of 9.335> t table 2.011. Thus Ha is accepted because of tcount> t table. Therefore, it can be concluded that word of mouth or independent variables partially have a significant effect on purchasing decisions or dependent variables.